Influence Of Copper And Zinc Stress On Protein Metabolism In Vigna Mungo (L.) Hepper - RADHA SOLANKI,; RAJESH DHANKHAR, (International Journal of Pharma and Bio Sciences, 2012)
The study was performed to assess the effect of copper and zinc ions on Vigna mungo (L.) Hepper grown hydroponically for seven days. A significant reduction was observed in free amino acid and protein levels of seedlings. Moreover, copper and zinc exposure resulted in apparent increase in specific activity of protease enzyme which was manifolds in comparison to control. The molecular response of the plant was studied by comparing the protein pattern of treated seedlings with control seedlings. SDS-PAGE of crude protein extract showed absence of some protein band in the region between 31.0 KD – 66.2 KD due to copper and zinc stress in comparison to control.